2016
DOI: 10.1111/jai.13090
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric differentiation between two juvenile tuna species [Thunnus thynnus (Linnaeus, 1758) and Euthynnus alletteratus (Rafinesque, 1810)] from the Eastern Mediterranean Sea

Abstract: Summary The main objective of this study was to analyse the differences in morphometric characteristics among specimens of Atlantic juvenile bluefin tuna Thunnus thynnus [12.2–46.5 cm fork length (FL)] and juvenile little tuna Euthynnus alletteratus (14.1–26.4 cm FL). A total of 353 bluefin tuna (young of the year) and 288 little tuna (young of the year) were collected from the commercial hand line fisheries in the eastern Mediterranean Sea between July and October of 2011–2013 with three round‐bent hook sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, a similar study in Tunisian waters revealed that fork length, standard length, and pectoral fin are important characteristics in differentiating between bluefin tuna populations Auxis rochei (Allaya et al 2016). Likewise, a study conducted by Karakulak et al (2016) demonstrated that there is a clear relationship between the length of the head and the length of the pectoral fin, the first predorsal, and the height of the second dorsal fin between Thunnus thynnus and E. alletteratus. Furthermore, Griffiths et al (2017) divulged a highly significant relationship between fork length-total length and length-weight among four Scombridae fish species (E. affinis, T. tonggol, R. kanagurta, and C. elegans).…”
Section: Discriminant Function Analysis (Dfa)mentioning
confidence: 85%
“…Furthermore, a similar study in Tunisian waters revealed that fork length, standard length, and pectoral fin are important characteristics in differentiating between bluefin tuna populations Auxis rochei (Allaya et al 2016). Likewise, a study conducted by Karakulak et al (2016) demonstrated that there is a clear relationship between the length of the head and the length of the pectoral fin, the first predorsal, and the height of the second dorsal fin between Thunnus thynnus and E. alletteratus. Furthermore, Griffiths et al (2017) divulged a highly significant relationship between fork length-total length and length-weight among four Scombridae fish species (E. affinis, T. tonggol, R. kanagurta, and C. elegans).…”
Section: Discriminant Function Analysis (Dfa)mentioning
confidence: 85%
“…Another study in Tunisian waters revealed that the pectoral fin, standard length, and fork length play an important roles to discriminate between the population of bullet tuna, Auxis rochei [22]. Additionally, [23] demonstrated a strong correlation of head length, pectoral fin length, first predorsal length, and second dorsal fin height between Thunnus thynnus and Euthynnus alletteratus. Likewise, the maximum value to separate among five populations of Clupisoma garua in DFA was function 1 as reported by [24] .…”
Section: Resultsmentioning
confidence: 99%
“…Little tunny, Euthynnus alletteratus (Rafinesque, 1810) is a pelagic and highly migratory fish of the family Scombridae that inhabits the tropical and subtropical coastal waters of both sides of the Atlantic Ocean. There are three main populations of E. alletteratus known in the Atlantic Ocean, located in the center-east, in the southeast and in the west of the Atlantic Ocean (Karakulak et al, 2016;Mele et al, 2016). It is considered an abundant fish species in the Brazilian Northeast coast (Lucena et al, 2004) with very little information regarding its parasitic fauna in this region (Alves & Luque, 2006).…”
Section: Introductionmentioning
confidence: 99%